Is the classical elephant trunk better than the frozen elephant trunk? - Schepens, Marc; Ranschaert, Willem; Vergauwen, Wim; Graulus, Eric; De Vos, Marie (Indian journal of thoracic and cardiovascular surgery, 2022)
Aortic diseases located in the ascending aorta, aortic arch or proximal descending aorta often require more than one surgical intervention depending on the type of pathology and its extent as well as future anticipated aortic problems. These obstacles were tackled in 1983 by Hans Borst with the introduction of the classic elephant trunk (cET). This was an outstanding and straightforward procedure. Since then, the cET was very often the first surgical approach for patients with extensive aortic pathology of the ascending aorta and arch extending into the downstream aorta. Thirteen years later, Suto and Kato introduced the frozen elephant trunk (fET) which was later on perfectionized by industry and applied in various ways by many surgical groups worldwide. Comparing the cET with the fET raises a lot of difficulties. The lack of randomization and the presence of procedural and complication-related limitations for each technique do not allow for definitive conclusions about the ideal procedure to treat complex aortic pathology. It would be very short-sighted to close all future discussions about the subject with this statement of the Hannover group made in 2011. Since both techniques and its results cannot be compared statistically due to the heterogeneity of patient groups, the lack of randomization, the difference in type and extent of pathology, the differences in surgical techniques, the learning curve in gaining experience in both techniques, and the lack of reporting standards, no scientific conclusion can be drawn as to which technique is most successful. Comparisons may even be considered futile. It is the purpose of this paper merely to make a descriptive observation of both techniques, to discuss some important elements of interest and to give some constructive and useful criticism.